2022
DOI: 10.1186/s13756-022-01110-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early antibiotic exposure on the risk of colonization with potential pathogens in very preterm infants: a retrospective cohort analysis

Abstract: Background Sepsis is one of the most important complications in preterm infants. For this reason, most preterm infants receive antibiotics during their first postnatal week. Since 2013, a weekly colonization screening has been installed in German neonatal intensive care units (NICUs), including multi-drug resistant organisms (MDRO) and pathogens with increased epidemic potential. We here investigated the impact of early antibiotic exposure on the colonization with these pathogens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…We found high rates of antibiotic treatment in our cohort with about 70% of all VLBWI exposed to antibiotics during their initial hospital stay and about 55% already exposed within the first 2 days of postnatal life. This is in line with previous reports showing rates up 80% of VLWBI receiving early antibiotics 6 7 26. However, the extremely high number of antibiotic-exposed infants within the first 2 days of postnatal life contrasts sharply with the reported incidence of culture-proven EOS of 1%–2%1 27 28 and the actual incidence of EOS in our cohort (clinical and culture-proven EOS amounting to 6.1%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found high rates of antibiotic treatment in our cohort with about 70% of all VLBWI exposed to antibiotics during their initial hospital stay and about 55% already exposed within the first 2 days of postnatal life. This is in line with previous reports showing rates up 80% of VLWBI receiving early antibiotics 6 7 26. However, the extremely high number of antibiotic-exposed infants within the first 2 days of postnatal life contrasts sharply with the reported incidence of culture-proven EOS of 1%–2%1 27 28 and the actual incidence of EOS in our cohort (clinical and culture-proven EOS amounting to 6.1%).…”
Section: Discussionsupporting
confidence: 91%
“…In addition to high mortality, neonatal sepsis is associated with a wide variety of severe complications during the neonatal period, such as bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), intraventricular haemorrhage (IVH) or necrotising enterocolitis (NEC), as well as poor neurodevelopmental outcome 1 5. For this reason, up to 90% of extremely premature infants receive antibiotics early after birth 6 7…”
Section: Introductionmentioning
confidence: 99%
“…This limitation was demonstrated in the study by Boyle et al ( 17 ) where infants prophylactically treated with kanamycin had higher incidence of kanamycin-resistant enteric gram-negative bacteria compared to controls. A second limitation is selective growth of other pathogenic bacteria ( 26 ). This limitation was demonstrated in the study by Siu et.…”
Section: Human Studies Of Early Antibiotics and Necmentioning
confidence: 99%
“…This could be related to the impact of the gut microbiome on the development of the immune system, thereby affecting children's resistance to respiratory infections. However, research by Bubser et al [ 17 ] found that early antibiotic treatment did not increase the risk of carrying potential pathogens in preterm infants. Yet, research by Chen et al [ 18 ] points out that early antibiotic exposure is associated with an increased risk of bronchopulmonary dysplasia in very low birth weight infants.…”
Section: Discussionmentioning
confidence: 99%